Assessment of the cytotoxicity of coumarin-3-carboxylic acid in human erythrocytes (Research, Society and Development, 2022)
The erythrocyte is a cell type that is highly susceptible to lipid peroxidation and hemolysis. In vitro cytotoxicity tests are often used to screen and determine the toxicity of various compounds, primarily to investigate direct effects on membrane integrity. Coumarins (1,2-benzopyrone) are part of a group of heterocyclic compounds present in several plant families. Numerous biological activities have been demonstrated for coumarins and their derivatives, including anti-inflammatory, antioxidant, anticancer and antimicrobial properties. The aim of the present study was to investigate for the first time the toxic profile of a coumarin derivative, 3-coumarin carboxylic acid, in cytotoxicity assays involving human erythrocytes. Solutions containing 3-coumarin carboxylic acid at concentrations of 50, 100, 500 and 1000 µg/mL were prepared. Human blood samples of types A, B and O were collected from healthy volunteers and submitted to cytotoxicity assessment in the face of hemolytic and anti-hemolytic activity assays. The tested substance was able to reduce lysis on human erythrocytes of blood types A, B and O at all concentrations tested. In the osmotic fragility assay, 3-coumarin carboxylic acid was also able to protect human erythrocytes against hemolysis, in blood types A, B and O, at concentrations of 50µg/mL and 100µg/mL. The in vitro cytotoxicity results indicate that 3-coumarin carboxylic acid showed a low percentage of hemolysis for human erythrocytes of blood groups A, B and O when in direct contact with these cells, being also able to protect the erythrocyte membrane, preventing hemolysis.